Is it all in my mind? psychogenic pain revisited - Giuseppe De Benedittis (Publiediting, 2008)
Psychogenic Pain does not imply that pain is simply caused by psychological factors only, as opposed to Somatogenic Pain. It refers to pain that can better be explained in a psychological language rather than in a physical one. Psychogenic Pain or Pain Disorder is a Somatoform Disorder (DSM-IV), rather rare (2%) though underestimated. Psychodinamics suggest that psychogenic pain expresses symbolically unconscious conflicts. Moreover, neuroimaging techniques and hypnosis have recently showed how thin the borderline is between real and imagined percepts. The new quantum physics and the theory of chaotic complex systems provide a new, exciting framework to explain the brain-mind interface, thus allowing to overcome the old and inadequate dicotomy between body and mind, between "somatogenic pain" and "psychogenic pain".